2019
DOI: 10.1021/acs.energyfuels.9b01678
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Gradual and Accelerated Oxidative Stability of Karanja Biodiesel and Biodiesel–Diesel Blends

Abstract: One of the major limitations that hinder widespread application of biodiesel in automotive engines is its poor oxidative stability, which in turn depends upon methyl ester constituents of biodiesel as well the storage conditions. Hence, a relative assessment of the oxidative stability of biodiesels across the different parts of the world is rather difficult. In the present work, oxidative stability of biodiesel based on the ASTM D4625 accelerated oxidative stability test is compared with that of gradual oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…All the WCO biodiesel samples with antioxidants easily met the biodiesel standard limits for viscosity even after 6 months of storage, while fresh WCO biodiesel fuel sample exceeded the highest limit set by the EN or ASTM standard in 6 months of storage period. In the case of fuel samples stored at 43 ℃, neat Karanja biodiesel crossed the maximum limit set by the ASTM standard specifications (ASTM D4625-16e1 ( 2016)) within 4 months of storage (Suraj et al 2019). Karavalakis et al (2011) reported that viscosity increases over 10 weeks of storage time for B10 with synthetic antioxidants (BHT, BHA, PG, PY, and TBHQ); all values are within the limit of standard.…”
Section: Kinematic Viscositymentioning
confidence: 82%
See 4 more Smart Citations
“…All the WCO biodiesel samples with antioxidants easily met the biodiesel standard limits for viscosity even after 6 months of storage, while fresh WCO biodiesel fuel sample exceeded the highest limit set by the EN or ASTM standard in 6 months of storage period. In the case of fuel samples stored at 43 ℃, neat Karanja biodiesel crossed the maximum limit set by the ASTM standard specifications (ASTM D4625-16e1 ( 2016)) within 4 months of storage (Suraj et al 2019). Karavalakis et al (2011) reported that viscosity increases over 10 weeks of storage time for B10 with synthetic antioxidants (BHT, BHA, PG, PY, and TBHQ); all values are within the limit of standard.…”
Section: Kinematic Viscositymentioning
confidence: 82%
“…The higher rate of increasing acid value of test samples in lower concentrations (100 and 250 ppm) and fresh biodiesel samples at stored conditions was due to a higher rate of secondary oxidation. After two months of storage periods at 43 °C, Karanja biodiesel without antioxidant failed to meet the biodiesel standard (ASTM D4625-16e1 ( 2016)) (Suraj et al 2019). The acid value increased over 10 weeks of storage time for B7, B10, and B20 with synthetic antioxidants (BHT, BHA, PG, PY, and TBHQ), but all values were within the limit of the standard according to Karavalakis et al (2011).…”
Section: Acid Valuementioning
confidence: 95%
See 3 more Smart Citations